ϴзбекстанның тунғыш профессоры - Сейтмуратов, Қ (SCIENCE and SOCIETY, 2023)
The article deals with the issues of Jadid and educational activities and pedagogical thoughts of the prom- inent Uzbek teacher and poet Abdirauf Fitrat.
Keywords: jadidism; enlightenment; school; madrasah; reform; independence